Sustaining Impacts When Transfers End : The Role of Women Leaders for Aspirations and Human Capital Investments - Macours, Karen; Vakis, Renos (World Bank, Washington, DC, 2017)
Sustainability of short-term interventions may depend on whether they manage to change families’ attitudes towards the future and related social norms. This investigation shows that role female models in very low-income settings of Nicaragua have an enormous impact in raising the bar for the rest of the community by increasing and sustaining in time basic standards in children education and health.